Acute inhibitory effect of alpha‐mangostin on sarcoplasmic reticulum calcium‐ATPase and myocardial relaxation. Issue 10 (7th June 2017) - Phungphong, Sukanya; Kijtawornrat, Anusak; de Tombe, Pieter P.; Wattanapermpool, Jonggonnee; Bupha‐Intr, Tepmanas; Suksamrarn, Sunit
Abstract: The benefits of α‐mangostin for various tissues have been reported, but its effect on the heart has not been clarified. This study aimed to evaluate the effects of α‐mangostin on cardiac function. Using a cardiac sarcoplasmic reticulum (SR) membrane preparation, α‐mangostin inhibited SR Ca 2+ ‐ATPase activity in a dose‐dependent manner (IC50 of 6.47 ± 0.7 μM). Its suppressive effect was specific to SR Ca 2+ ‐ATPase but not to myofibrillar Ca 2+ ‐ATPase. Using isolated cardiomyocytes, 50 μM of α‐mangostin significantly increased the duration of cell relengthening and increased the duration of Ca 2+ transient decay, suggesting altered myocyte relaxation. The relaxation effect of α‐mangostin was also supported in vivo after intravenous infusion. A significant suppression of both peak pressure and rate of ventricular relaxation (– dP / dt ) relative to DMSO infusion was observed. The results from the present study demonstrated that α‐mangostin exerts specific inhibitory action on SR Ca 2+ ‐ATPase activity, leading to myocardial relaxation dysfunction.